Estimating the Contribution of the Summer Traffic Peak to PM2.5, NOx, and NMVOCs - Petra Dolšak Lavrič; Andreja Kukec (Atmosphere)
Air quality is becoming an important asset of modern society. Europe is adopting regulations that will enable better air quality for residents and encourage detailed study of emissions sources. Transport is recognized as a flourishing sector with the yearly growth of vehicle numbers. Even if the transport emissions trend slightly decreases, there is a concern that the increase in vehicle numbers on the road will slow down the process. Data from the bottom-up approach, estimating emissions from transit vehicles and tourism activities, was identified as a critical knowledge gap. Our study identifies and evaluates the issue of vehicle congestion on the roads during the summer, primarily driven by transit demands and tourism activities. The methodology to capture an understanding of traffic-related emissions from the summer vehicle peak was developed. Summer traffic peak was estimated by comparing the summer vehicle numbers with those of other parts of the year. Vehicle numbers were recognized by vehicle counters located on a Slovenian highway junction in the year 2021. Moreover, the study also revealed the emissions from the summer traffic peak, calculated by the COPERT emission model. We observed that, on an average summer day, there are up to 11,520 additional vehicles on Slovenian roads. It was estimated that the peak in summer passenger cars contributes up to 41,875 kg, 9542 kg, and 3057 kg of NOx, NMVOCs, and PM2.5 emissions. The maximum emissions of NOx and PM2.5 from light duty vehicles are 17,108 kg and 867 kg. There are non-negligible emissions of NMVOCs from motorcycles and these represent up to 3042 kg.